A proposed collection development policy and prototype integrated library system for the technical library and database center of Philippine Batteries Inc. - Agnar, Aldus T., 1985; Dorado, Dan Anthony D.; Lacsamana, Roel Ellis V. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2014)
This study aimed to develop an Integrated Library System (ILS) prototype and propose a Collection Development Policy (CDP) for the establishment of the Technical Library and Database Center (TLDC) of the Philippine Batteries, Inc. (PBI).
PBI is a battery manufacturing company with continuous research and process and product development. Their Technical Department houses the Documents and Records Control Center (DRCC) and the Technical Database Management System (TDMS) is where most of the library's resources are stored. PBI envisions strengthening its research and development capability by establishing the library's collection and a library system is needed to manage the collection.
Preliminary study ocular inspection was done to assess the current status of the library and its collection. Both structured and informal interviews were done to establish user preference on the system to be developed.
The User-Centered Systems Design Framework served as the conceptual framework of the study. The ILS prototype was developed following the Systems Development Life Cycle. In developing the system, XAMMP, Bootstrap (front-end-framework), MySQL and phpMyAdmin were used.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Philippine Batteries Inc; Collection development (libraries).; Integrated library systems(Computers) -- Philippines